Characterisation of protein phosphorylation in Arabidopsis thaliana and Chlamydomonas reinhardtii based on affinity chromatography and mass spectrometry - Wolschin, Florian (2006)
Reversible protein phosphorylation is of key importance for several mechanisms of life. However, the low abundance of phosphorylated proteins hinders investigations following this direction. To circumvent this problem a new method for the enrichment of phosphorylated proteins out of complex protein mixtures was developed. This method relies on the affinity of the phosphate group towards aluminum hydroxide and was termed MOAC (Metal Oxide Affinity Chromatography). Successful phosphoprotein enrichment even from highly complex protein mixtures was confirmed by separation of phosphorylated from non-phosphorylated standard proteins, detection using a phosphate-specific fluorescent stain, ICP-MS (Inductively Coupled Plasma Mass Spectrometry), and antibodies. To identify phosphopeptides and protein phosphorylation sites proteins were digested with an endoproteinase and subjected to LC/MSn analysis. The determination of protein phosphorylation sites was achieved by making use of the distinct neutral loss of phosphoric acid from peptides phosphorylated on serine or threonine during fragmentation in an ion trap mass spectrometer. However, it was observed that also other posttranslational modifications such as methionine oxidation can mimic phosphorylation when using such data-dependent neutral loss scans. Remedies were defined to circumvent this problem leading to more reliable phosphorylation site identification. The combination of MOAC and a neutral loss driven MS3 approach showed to be highly useful for investigations on plant protein phosphorylation. In one of the first non-targeted phosphoproteomics approaches in plant science this combined approach was applied to enrich phosphoproteins of A. thaliana and of C. reinhardtii leading to the identification of over 40 phosphopeptides, 27 phosphorylation sites, and over 30 phosphoproteins. In addition, over 300 putative phosphoproteins were identified. In a targeted analysis the speculative in vivo phosphorylation site of the metabolic key enzyme phosphoenolpyruvate carboxylase in A. thaliana could be confirmed. While the detection of phosphorylation and the determination of phosphorylation sites are very important to get a first impression whether or not a protein can be influenced by phosphorylation, quantification of phosphorylation delivers more detailed information on protein regulation by phosphorylation. Using an approach involving ICP-MS it was possible to monitor the overall protein phosphorylation degree for different developmental stages of A. thaliana. These values were compared to the degree of phosphorylation of proteins in C. reinhardtii. This comparison shows that protein phosphorylation is most abundant in rapidly dividing tissue and lowest in dormant seeds. To monitor phosphorylation of key metabolic enzymes under different physiological conditions, a robust method for relative quantification of changes in protein phosphorylation on a linear ion trap was also developed. It was used to investigate a speculative connection between temperature and phosphorylation of sucrose-phosphate synthase (SPS) and to determine the stoichiometry of phosphorylation for the in vitro phosphorylated enzyme. The results indicate that temperature has a profound effect on the phosphorylation level of SPS by influencing the activity or abundance of the kinase responsible for SPS phosphorylation.
Keywords: Hochschulschrift